Neoliberal governmentality and the (de)politicisation of LGBT rights: The case of the European Union in Turkey. (May 2019) - Muehlenhoff, Hanna L
The European Union (EU) praises itself for being a promoter of lesbian, gay, bisexual, and transgender (LGBT) rights in the world. It supports LGBT organisations abroad with the European Instrument for Democracy and Human Rights (EIDHR). Yet, the EIDHR has come under scrutiny by scholars arguing that it is based on neoliberal rationalities and depoliticises civil society. The literature analyses the EU's documents but does not study funding in practice. Moreover, it has a narrow understanding of politicisation failing to include insights from feminist and queer literature. To problematize the EU's policy, we need to analyse it in the sites it intervenes in. It is unclear whether and how the EIDHR depoliticises LGBT organisations and issues. Studying the case of Turkey, I argue that the EU's support of LGBT organisations had ambiguous effects which are not necessarily the ones intended by the EU nor the ones expected by the governmentality literature. The EU's funding depoliticised the organisations in the sense that they looked less political and more transparent. Yet, this helped making LGBT rights' claims more legitimate within Turkey's political struggles. At the same time, EU funding created conflicts within the LGBT movement about the question of Western external funding and neoliberal co-optation.